The Validity of Goods/Services Contracts Signed by Commitment Making Officials Who Do Not Have A Certificate of Competency - Hermansyah, Hermansyah; Saleh, Mohammad (Dinasti Research, 2024)
This research discusses the validity of goods/services procurement contracts signed by Commitment Making Officials (PPK) without a certificate of competence, in accordance with the provisions of Presidential Regulation No. 16/2018. This regulation requires PPK to have a certificate of competence by December 31, 2023, but many PPKs have not yet met this requirement. Through LKPP Circular Letter (SE) Number 1 of 2024, relaxation of this requirement is given, allowing the assignment of PPK from Other Personnel with basic certificates. This research uses a normative method with a conceptual and statutory approach, analyzing the legal implications of the relaxation. The results show that contracts signed by PPK without a certificate of competence can be considered